Frequency optimization of nozzle guide vane in the low-pressure turbine system. Issue 1 (1st March 2022) - Robak, R; Szczepanik, M; Rulik, S
Abstract: The aim of the article is to present the approach for modal optimisation of nozzle guide vane in the low-pressure turbine system of aircraft engine. Described analysis assumption related to the finite element model definition, meta-model estimation and optimisation process itself. Goal function has been determined basing on Campbell diagram. Typical approach to solve modal analysis for mentioned structure is full three-dimensional model that is time consuming. For optimisation purposes employed two dimensional one in order to make the process more robust (element types with support of Fourier series). This approach is reducing degree of freedom quantity and is still capable to consider non-axisymmetric structure behaviour. The article provides relationship between geometrical features of nozzle and frequency change.